2020
DOI: 10.1016/j.exer.2020.108071
|View full text |Cite
|
Sign up to set email alerts
|

Viral delivery of multiple miRNAs promotes retinal ganglion cell survival and functional preservation after optic nerve crush injury

Abstract: Bone marrow mesenchymal stem cell (BMSC)-derived small extracellular vesicles (sEV) but not fibroblast sEV provide retinal ganglion cell (RGC) neuroprotection both in vitro and in vivo, with miRNAs playing an essential role. More than 40 miRNAs were more abundant in BMSC-sEV than in fibroblast-sEV. The purpose of this study was to test the in vitro and in vivo neuroprotective and axogenic properties of six candidate miRNAs (miR-26a, miR-17, miR-30c-2, miR-92a, miR-292, and miR-182) that were more abundant in B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 52 publications
(59 reference statements)
0
8
0
Order By: Relevance
“…In this study, we used lipofectamine to deliver miRNA mimics/AntagomiRs into RGC, an approach feasible in vitro but less so in vivo. Alternative approaches would need to be considered, and include the use of viral vectors [ 43 ] or exosome/small extracellular vesicle carriers [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used lipofectamine to deliver miRNA mimics/AntagomiRs into RGC, an approach feasible in vitro but less so in vivo. Alternative approaches would need to be considered, and include the use of viral vectors [ 43 ] or exosome/small extracellular vesicle carriers [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In an optic nerve crush rat model, Mead et al found that exosomes protect retinal neurons by exosome delivery, and that the protective effects were dependent on miRNAs for the diminished therapeutic effects of MSC-Exos after knockdown of Argonaute-2 [ 35 ]. Thereafter, they identified six candidate miRNAs (miR-26a, miR-30c-2 and miR-92a; miR-292, miR-17 and miR-182) and expressed a combination of three of these candidate miRNAs to treat optic nerve crush injury, finding that these candidate miRNAs promoted RGC survival [ 40 ]. Actually, miR-146a has mostly been documented in the context of central nervous system (CNS) diseases, especially in Alzheimer's disease (AD).…”
Section: Discussionmentioning
confidence: 99%
“…Electroretinography (ERG) was performed as described by us previously (Mead et al ., 2020). Briefly, rats were dark adapted for 12 hours and after anaesthesia eyes were dilated with tropicamide.…”
Section: Methodsmentioning
confidence: 99%